2019
DOI: 10.3390/ma12193131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gypsum on Hydration and Hardening Properties of Alite Modified Calcium Sulfoaluminate Cement

Abstract: Calcium sulphoaluminate cement (CSA) has the characteristics of quick hardening, high early strength and high impermeability, however its strength growth persistence in the middle and late stages (after the age of 3 days) is poor. In order to improve this disadvantage, the pilot production of alite (C3S) modified CSA (AMCSA) clinker was carried out by liquid phase manipulation and barium ion doping technology. The effects of different dosages of gypsum on the hydration and hardening properties of AMCSA, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…the actual CaO content was similar. Previous studies reported that the development of early strength increased as the SO3 content increased in the range of less than 5% [36][37][38]. Figure 9a shows the chloride penetration depth of each concrete mix by age.…”
Section: Porosity Of Inner Concretementioning
confidence: 91%
“…the actual CaO content was similar. Previous studies reported that the development of early strength increased as the SO3 content increased in the range of less than 5% [36][37][38]. Figure 9a shows the chloride penetration depth of each concrete mix by age.…”
Section: Porosity Of Inner Concretementioning
confidence: 91%
“…Calcium sulfoaluminate cement (CSAC), which has been manufactured and used on a large scale in China since the 1970s, is considered environment-friendly with low CO 2 emissions [ 1 , 2 , 3 , 4 ]. Compared with Portland cement, CSAC exhibits a shorter setting time, faster hardening, higher early strength, better durability, etc., and is widely used in various special areas of engineering, such as rapid repair engineering, ocean engineering, winter construction and so on [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Klein and Metha reported that various hydrates can be produced depending on the molar ratios of Al 2 O 3 /SO 3 and CaO/SO 3 in the CaO-Al 2 O 3 -SO 3 system [23], where a high Al 2 O 3 component exhibits quick-setting and early strength, a high CaO component exhibits expandability, and a high SO 3 component exhibits high strength characteristics [24]. The key factors for the hydration of CSA cements vary according to the ingredients and composition of the hauyne clinkers, the reactivity of the externally incorporated gypsum, the type of mixture, and the mixing and curing conditions.…”
Section: Introductionmentioning
confidence: 99%